Development of early detection of low-birth-weight instrument based on maternal risk factors: A mixed-methods study - Sri Utami; Rekawati Susilaningrum; Nursalam Nursalam; Erna Siti Zulaecha; Sri Rahayu (Faculty of Nursing Universitas Padjadjaran, 2023)
Background: Babies born with low birth weight (LBW) are at a higher risk of experiencing health problems. The absence of quick and reliable instruments to detect LBW conditions can significantly impact the growth and development of newborns. Purpose: This study aims to develop an instrument to detect the incidence of LBW based on mother’s risk factor. Methods: In this study, mixed-methods research was conducted, consisting of qualitative and quantitative stages. A total of 20 participants participated in Focus Group Discussions (FGDs) during the qualitative stage, and 321 respondents took part in the quantitative stage. During the qualitative stage, the process of labeling, synthesizing significant codes, and theoretical integration was carried out. Furthermore, at the quantitative stage, the calculation of the cut-off point using receiver operating characteristic (ROC) analysis was performed. Result: Four indicators were added in newly developed instrument; there are currently ten indicators based on results of our FGD with the experts (OR/score: 74.395/10, 15.557/2, 13.877/2, 9.952/2, 7.203/1, 2.756/1, 2.532/1, 1.280/1, 1.268/1, and 1.163/1). Instrument was tested on 321 samples; it was able to detect 111 (88.1%) cases from a total 123 (38.3%) cases of LBW (p=0.000). Cut-off point determination used Receiver Operating Characteristic (ROC) curve; any score greater than 3 was predicted with LBW incidence (AUC=0.952, 95% CI 0.923-0.973). Conclusions: LBW could be predicted by our newly developed instrument. These finding could help health workers or policy makers to reduce the LBW incidence by early detection. Further study is needed to determine the ideal screening time to maximize the usage of this instrument.